2005
DOI: 10.1007/bf03016282
|View full text |Cite
|
Sign up to set email alerts
|

Duration of analgesia is similar when 15, 20, 25 and 30 mL of ropivacaine 0.5% are administered via a femoral catheter

Abstract: P Pu ur rp po os se e: : This dose-response study was designed to determine the most appropriate dose of ropivacaine 0.5% injected via an indwelling femoral catheter for perioperative peripheral analgesia for total knee replacement (TKR).M Me et th ho od ds s: : 84 patients were allocated randomly to four groups and received, via a femoral catheter, either 15, 20, 25 or 30 mL of ropivacaine 0.5% in a double-blind fashion. An anterior sciatic block with 20 mL bupivacaine 0.5% was also performed. The evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
14
0
4
Order By: Relevance
“…The use of GBP with regional anesthesia (spinal or epidural analgesia, and peripheral nerve blocks) as the primary surgical modality, provides a robust neuronal blockade for hours after surgery. Spinal anesthesia was chosen as the primary anesthetic modality and the peripheral (ie, femoral and sciatic) nerve blocks were adjuncts for postoperative pain (12±3 h) (38). Table 2 and Figure 1 demonstrate the effectiveness of our spinal and peripheral nerve blockade regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of GBP with regional anesthesia (spinal or epidural analgesia, and peripheral nerve blocks) as the primary surgical modality, provides a robust neuronal blockade for hours after surgery. Spinal anesthesia was chosen as the primary anesthetic modality and the peripheral (ie, femoral and sciatic) nerve blocks were adjuncts for postoperative pain (12±3 h) (38). Table 2 and Figure 1 demonstrate the effectiveness of our spinal and peripheral nerve blockade regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral and sciatic nerve blocks were performed using a nerve stimulator and ultrasound technique to localize the nerves at less than 0.5 mA. Ropivacaine 0.5% (20 L), with an approximate mean duration of action of 15 h, was deposited adjacent to each nerve (38). Spinal anesthesia was performed in the lateral decubitus or sitting position.…”
Section: Methodsmentioning
confidence: 99%
“…One study also showed that the time to first analgesic request was significantly longer with parecoxib compared with placebo [14] (see Table 1). [19] Inconclusive Ropivacaine via femoral catheter [117] NS Bupivacaine via femoral catheter [35] NS Spinal diamorphine [42] NS Spinal morphine [43] NS Lumbar epidural ketamine [52] NS Lumbar epidural ropivacaine [50,53] Inconclusive Route and method of drug administration IV vs IM strong opioid [23] NS IV PCA vs IM strong opioid [24] IM superior for moderate pain scores Surgical approaches Medial trivector approach [61], Subvastus approach [62], vs parapatellar approach NS Posterior cruciate ligament (PCL) surgery during TKA: different surgical approaches [63] PCL released surgery inferior to other approaches Midvastus approach vs medial parapatellar approach [64] Midvastus superior at rest and on movement…”
Section: Cox-2-selective Inhibitorsmentioning
confidence: 99%
“…A longer-acting solution of ropivacaine 0.5% (20 mL), deposited adjacent to each nerve, will produce a mean anaesthetic duration of action of 15 hours. 159 Occasionally it becomes difficult to predict the level of motor impairment that accompanies single-shot nerve blocks. This is a significant consideration for patient safety if ambulation on postoperative day 0, or early on postoperative day 1, is desirable.…”
Section: Single-shot Peripheral Nerve Blocksmentioning
confidence: 99%